EXAMINING THE IMPACT OF STRUCTURAL BREAKS ON PRICE DISCOVERY EFFICIENCY: EVIDENCE FROM THE INDIAN EQUITY FUTURES MARKET - Adish Kumar,; Kapil Gupta, (Copernican Journal of Finance & Accounting, 2022)
The current study aims to examine the impact of structural breaks on price discovery efficiency of Indian equity futures market. Global financial crisis, change of Government, demonetization and COVID-19 are identified as significant events. Data is divided into sub-samples of pre and post event period to study the impact of these events on price discovery efficiency of the Indian equity futures market. Unit root test is used to check stationarity of data. Granger causality test, Johansen’s cointegration test and Vector error correction methodology (VECM) are used for analysis. During full sample period, it is observed that there is a significant bi-directional causality between cash and futures markets and cash market leads futures market in price discovery. In addition, global financial crisis triggered volatility in Indian equity futures market, which reduced its price discovery efficiency, whereas, after change in Government, bidirectional transmission of information restored between cash market and futures market. Furthermore, futures market played a leading role in absorbing volatility triggered by demonetization. COVID-19 did not significantly affect price discovery efficiency of Indian equity futures market.